CT and MRI of intracranial extramedullary hematopoiesis: Two case reports - Visrutaratna P. (2014)
Intracranial extramedullary hematopoiesis is rare. We report CT and MR imaging findings of intracranial extramedullary hematopoiesis in two children with thalassemia. The first child had three extraaxial masses along the falx cerebri and tentorium and an extraaxial mass in the left temporal fossa. The masses at the tentorium had exterted pressure on the fourth ventricle resulting in dilatation of the lateral and third ventricles. The second one had a mass at the skull base arising from the sphenoid and ethmoid sinuses with extension into the anterior cranial fossa, which compressed the intracanalicular portions of the optic nerves.